New Algorithm for Fast Processing RFID System in Container Terminal - Evizal Abdul Kadir; Siti Mariyam Shamsuddin; Detri Karya; Sri Listia Rosa (Institute of Advanced Engineering and Science, 2016)
The growth of world economic and increasing of trading in most of countries has impact to the number of containers export and import between countries. Some of container terminal is very busy to handle high volume of container movement. Conventional operational procedures have difficulties to handle containers movement then make slow and some issues in terminal operation for container clearance. This paper discus on proposing new algorithm to the current container terminal management system used RFID technology for fast processing and clearance. Container Terminal Management System (CTMS) is a system for port management and interface to the RFID system that used to identify container e-seal, truck and driver identity. Lack of communication and interfacing protocol made slow response during request or reply of message to the gate operator. Proposed algorithm with new procedure of request to CTMS made faster response and avoid inaccuracy of detecting container e-seal. Results of implementation new algorithm have improved to the productivity and efficiency of container terminal. Testing and implementation of this proposed system conducted in a private container terminal in Malaysia.